2020
DOI: 10.3390/ijerph17124585
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association between Trauma Exposure and Work-Related Outcomes in Women Veterans

Abstract: Women veterans have high rates of trauma exposure, including military sexual trauma (MST), which are associated with numerous health and psychosocial consequences. However, associations between trauma history and work-related outcomes are less well-characterized. We examined whether military-related and non-military trauma types were associated with work-related outcomes and whether posttraumatic stress disorder (PTSD) and depression symptoms mediated these associations. A total of 369 women veterans completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Although the relationship between deployment stressors, depression, and work functioning in women was identified and emphasized in a prior study [23], current findings suggest that the effect of deployment stressors and depression on work functioning persists over a longer timeframe. These findings are consistent with another study that found that women veterans who endorsed sexual assault during adulthood experienced worse occupational functioning one year later [65]. The finding that the strongest predictors of the decrement in work functioning, deployment sexual harassment and depression, are more prevalent in veteran women than men, support the value of additional support with regard to women's work functioning.…”
Section: Discussionsupporting
confidence: 90%
“…Although the relationship between deployment stressors, depression, and work functioning in women was identified and emphasized in a prior study [23], current findings suggest that the effect of deployment stressors and depression on work functioning persists over a longer timeframe. These findings are consistent with another study that found that women veterans who endorsed sexual assault during adulthood experienced worse occupational functioning one year later [65]. The finding that the strongest predictors of the decrement in work functioning, deployment sexual harassment and depression, are more prevalent in veteran women than men, support the value of additional support with regard to women's work functioning.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, given the fit of the alternative model, it is more probable that the appearance of PTSD cases explains the unemployment condition. This finding is novel in the literature reviewed and supports ideas such as the lack of clarity when the stress-unemployment cycle could begin [7,31], and the relationship between stressors, unemployment and mental health tends to be interdependent once it starts [7,9,32], in refugees [33,34], immigrants [35], men [36] and women veterans [37], and social workers, to name a few cases. For example, studies conducted on Iraqi refugees show that exposure before and after the event predicts unemployment by 91% [7].…”
Section: Discussionsupporting
confidence: 56%
“…They may also experience demoralization 1 related to inadequate support or seeing their contributions as ineffective. The impact of these types of experiences has been well documented in contexts such as military service, where both isolated and cumulative trauma exposure is strongly associated with high psychiatric symptom burden, as well as decreased occupational functioning and workplace participation [2][3][4] . Understanding how such occupational stressors affect HCW/FR is important to identify risks to HCW/FR and to our health care system, and develop strategies to reduce those risks 5 .…”
Section: Introductionmentioning
confidence: 99%